Nedocromil sodium and diphenhydramine HCl ameliorate exercise-induced arterial hypoxemia in highly trained athletes - Coyle, M. A.; Goss, C. S.; Manz, W. J.; Greenshields, J. T.; Chapman, R. F.; Stager, J. M. (Physiological Reports, 2022)
Introduction: Exercise-induced arterial hypoxemia (EIAH) has been observed in highly trained endurance athletes during near maximal exercise, which may be influenced by a histamine-mediated inflammatory response at the pulmonary capillary-alveolar membrane. In order to test this hypothesis, we examined whether the mast cell stabilizer nedocromil sodium (NS) and H1-receptor antagonist diphenhydramine HCL (DH) would ameliorate EIAH and mitigate the drop in arterial oxyhemoglobin saturation (SaO2) during intensive exercise. Methods: Seven highly trained male cross country runners (age, 21 ± 2 years; VO2max, 74.7 ± 3.5 ml/kg/min) participated in the study. All subjects completed a maximal exercise treadmill test to exhaustion, followed by three 5-min constant-load exercise bouts at 70%, 80%, and 90% VO2max. Prior to testing, subjects received either placebo (PL), NS, or DH. Results: Compared to PL, there was a significant treatment effect on SaO2 (p < 0.001) for both NS and DH during both constant-load exercise and at VO2max. Post hoc tests revealed SaO2 values, compared to PL, were significantly higher at VO2max and during DH trials and higher with NS at constant-load intensities except at 70% (p = 0.13). Conclusion: The findings provide further evidence that histamine contributes directly or indirectly to the development of EIAH during intense exercise in highly trained athletes.